Effect of Different Washing Cycles on the Quality of Pangasius hypophthalmus Surimi - Hassan, M. A.; Balange, A. K.; Senapati, S. R.; Martin Xavier, K. A. (Fishery Technology, 2017)
Pangasius is a fish with low cost and round the yearavailability, which can be an alternate raw materialto regular marine fish species like pink perch andcroaker. Yellow discolouration of meat is the mostserious problem in marketing Pangasius as fillet.There is a need to develop an alternative ways ofutilizing Pangasius and making surimi is one of thealternatives. Therefore attempts have been made inthe present investigation to optimize the process ofsurimi preparation from Pangasius hypophthalmus.Effect of different washing cycles i.e., one, two, threeand four washes with 1: 3 mince to water ratio onthe quality of Pangasius surimi was investigated. Itwas found that among the different washing cycles,third and fourth washing cycles have resulted in thehighest gel strength and lowest expressible moistureof Pangasius surimi as compared with control andother treatments. The sodium dodecyl sulphatepolyacrylamide gel electrophoresis (SDS-PAGE)study revealed disappearance of myosin heavychain (MHC) in the surimi gel obtained with thirdand fourth washing cycle indicating good crosslinking. With increasing washing cycle whiteness ofsurimi was also improved. Sensory evaluationindicated highest overall acceptability for surimiobtained with third and fourth washing. However,the quality of surimi obtained from third and fourthwashing was not different. Therefore, it can beconcluded that three washing cycles with 1:3 mince:water ration can be optimum for making goodquality surimi from Pangasius.